2020
DOI: 10.24321/2349.2880.201909
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Practices and Stress among School Adolescents in Delhi

Abstract: Background: Stress is now seen as a "lifestyle crisis" and affects any and every individual regardless of the stage of life they are in. It needs to be managed through life style modification. Objectives: To determinegender differences among lifestyle practices,the relationships among perceived stress and different lifestyle practices, and effective life style practices (coping strategies) to manage stress. Methodology: It is school based cross-sectional study, conducted among adolescents of two conveniently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
3
5
2
2
Order By: Relevance
“…Amongst several demographic factors, the present study found that the higher the age the more the students were likely to get stress, and this finding of significant association between the age and academic stress was supported by a previous studies in India (Jayanthi et al, 2015;Watode et al, 2015). It can be said that when the age increases the academic pressure from others and expectations of oneself and others also increases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Amongst several demographic factors, the present study found that the higher the age the more the students were likely to get stress, and this finding of significant association between the age and academic stress was supported by a previous studies in India (Jayanthi et al, 2015;Watode et al, 2015). It can be said that when the age increases the academic pressure from others and expectations of oneself and others also increases.…”
Section: Discussionsupporting
confidence: 86%
“…The present study also demonstrated that adolescents of literate mother are less likely to have academic stress compared to their counterparts and similar to this a study in India had also indicated a significant association between mother's education level and the academic stress of adolescents (Watode et al, 2015). Another Indian study also found an association between father's education and the academic stress of adolescents (Deb et al, 2015); however, the present study did not have such a finding.…”
Section: Discussionsupporting
confidence: 84%
“…[ 26 ] In the present study, 68% of adolescent girls reported perceived stress. It is difficult to compare the findings of the present study with the existing literature, due to differences in the scale used for assessment of stress, but our findings are comparable with some of the existing studies which have reported perception of stress among 89.7%[ 27 ] or which have reported mean PSS scores for adolescents. [ 28 ]…”
Section: Discussionsupporting
confidence: 61%
“…Stres pada remaja sekolah di India berdasarkan penelitian Watode, dkk. 6 didapatkan sebanyak 70% faktor penyebabnya adalah akademik, diikuti dengan faktor teman (3,0%), keluarga (11,8%), guru (6,3%) dan faktor lainnya (49,7%).…”
Section: Pendahuluanunclassified